Experience with bruxism in the everyday oral implantology practice in the Netherlands: a qualitative study. Issue 1 (December 2018) - Thymi, Magdalini; Rollman, Annemiek; Visscher, Corine; Wismeijer, Daniel; Lobbezoo, Frank
Abstract Objective To explore how bruxism is dealt with by accredited oral implantologists within daily clinical practice. Materials and methods Nine semi-structured interviews of oral implantologists practicing in non-academic clinical practices in the Netherlands were performed, and thematic analysis was conducted using a framework-based approach. Results Oral implant treatments in bruxing patients were a generally well-accepted practice. Complications were often expected, with most being of minor impact. Contradictive attitudes emerged on the topic of bruxism being an etiologic factor for peri-implant bone loss and loss of osseointegration. Views on the ideal treatment plan varied, though the importance of the superstructure's occlusion and articulation features was repeatedly pointed at. Similarly, views on protective splints varied, regarding their necessity and material choice. Bruxism was diagnosed mainly by clinical examination, alongside with patient anamnesis and clinician's intuition. There was little attention for awake bruxism. Discussion Bruxism was generally not considered a contraindication for implantological treatments by accredited oral implantologists. Views on the interaction between bruxism and bone loss/loss of osseointegration varied, as did views on the ideal treatment plan. Conclusions There is a need for better understanding of the extent to which, and under which circumstances, sleep and/or awake bruxism can be seen as causal factors for the occurrence of oral implant complications.